Metacognition skills to Basic fourth Grade Pupils and its Relationship with Achievement Goals Orientation - القاضي, لمى (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This study aimed at assist the level of Metacognition skills in social studies subject and achievement goals orientation to basic fourth grade pupils, and the relationship them. For that, the descriptive method was used, and prepared a reliable validate scale to measure Achievement Goals Orientation. The simple random sample consisted of (150) pupils in Lattakia city schools. The results showed that pupils’ metacognition skills were high (totally), and skill (monitoring, guidance, and the executive processing of the difficulties facing the achievement of the tasks) ranked first, followed by followed by (planning), and (metacognitive awareness) ranked last, while (self- evaluation) skill was low. In addition, There were correlational relationship between that metacognition skills in social studies subject and achievement goals orientation overall and its sub-domain (Performance-Approach, Mastery-Approach), but there were no correlational relationship between pupils’ metacognition skills and Goals (Mastery-Avoidance, Performance-Avoidance) So, the research recommended in the light of the results of study to Necessity of the use of metacognition skills and achievement goals orientation among pupils for development of learning outcomes in social studies subject.